Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1080/17458080701724943
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of LaF3: Yb3+,Ln3+nanoparticles with improved upconversion luminescence

Abstract: /Tm 3þ co-doped LaF 3 nanoparticles with upconversion luminescence properties were prepared via the co-precipitation method, followed by heat treatment at different temperatures in the range of 180 C to 600 C. We investigated the influence of heat treatment temperatures on the size, morphology, and upconversion luminescence intensity of the nanoparticles. Significant increases of the particle size and upconversion luminescence intensity of the nanoparticles were observed with increasing heat treatment temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Shen et al demonstrated that LaF 3 :Yb 3+ ,RE 3+ (RE=Er and Tm) NPs prepared via a hydrothermal co-precipitation method, followed by heat treatment at 180°C, 400°C, and 600°C separately. This investigation showed that the UCL intensity and particle size of these NPs were enhanced by increasing heat treatment temperatures 117. An elegant study by Zhang et al introduced a general solution-based hydrothermal technique for generation of well-controlled morphologies nanoarray crystals of sodium lanthanide fluorides.…”
Section: Ucnpsmentioning
confidence: 97%
See 1 more Smart Citation
“…Shen et al demonstrated that LaF 3 :Yb 3+ ,RE 3+ (RE=Er and Tm) NPs prepared via a hydrothermal co-precipitation method, followed by heat treatment at 180°C, 400°C, and 600°C separately. This investigation showed that the UCL intensity and particle size of these NPs were enhanced by increasing heat treatment temperatures 117. An elegant study by Zhang et al introduced a general solution-based hydrothermal technique for generation of well-controlled morphologies nanoarray crystals of sodium lanthanide fluorides.…”
Section: Ucnpsmentioning
confidence: 97%
“…In this method, unlike the thermal decomposition that mainly occurs in organic solvents, water-based media can be applied, and this moderate system allows some biocompatible chelating ligands such as sodium citrate and ethylene diamine tetra acetate (EDTA) cover the nanocrystals instead of long chain non-biocompatible organic ligands 113,114. Moreover, several studies have reported hydrothermal synthesizing in high temperatures and pressure reaction conditions 115117. It is likewise the thermal decomposition method that generates different morphologies and architectures by using and tuning different substances, solvents, and adjusting reaction time and temperature.…”
Section: Ucnpsmentioning
confidence: 99%
“…And subsequently, it is concluded that the most efficient infrared-to-visible upconversion phosphors are Yb/Er or Yb/Tm co-doped fluorides, such as hexagonal phase NaYF 4 [6,7], LaF 3 [8,9], and orthorhombic phase YF 3 [10], GdF 3 [11]. Especially in the past few years, the NaYF 4 -based phosphors, as the highest efficient upconversion phosphors, with different morphologies and different dopants have been widely investigated, based on various synthesis procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Research on upconversion nanocrystals increased exponentially over the past several years (e.g., in 2000, one article on upconversion nanomaterials was published, in 2009, it have been 57) as the extremely attractive prospects for applications of these materials in bioanalytics [ 3 ], (cancer) therapy [ 4 ], and electro-optics [ 5 ]. And subsequently, it is concluded that the most efficient infrared-to-visible upconversion phosphors are Yb/Er or Yb/Tm co-doped fluorides, such as hexagonal phase NaYF 4 [ 6 , 7 ], LaF 3 [ 8 , 9 ], and orthorhombic phase YF 3 [ 10 ], GdF 3 [ 11 ]. Especially in the past few years, the NaYF 4 -based phosphors, as the highest efficient upconversion phosphors, with different morphologies and different dopants have been widely investigated, based on various synthesis procedures.…”
Section: Introductionmentioning
confidence: 99%
“…A principal vantagem no uso desse polímero, e no caso desse trabalho, além da sua grande aplicabilidade, é sua abundância, podendo ser obtido a partir da reciclagem de biomassa ou como subproduto de celulose. 38 HPMC também tem sido foco de estudo na formação de compósitos com nanopartículas de metais 39,40 , no uso de materiais bactericidas 41,42 e agentes curativos 43,44 . Essas aplicações já estabelecidas unidos as propriedades do polímero, que não absorve nem emite nos comprimentos de onda de ambos os fenômenos (UC e RPS), motivaram a aplicação nanopartículas que apresentam o fenômeno de upconversion em polímeros de forma a facilitar sua aplicação.…”
unclassified